IMPACT OF SOCIAL MEDIA USE ON ADOLESCENT MENTAL HEALTH - Susmita Saha (EPH-International Journal of Humanities and Social Science, 2026)
In the 21st century, family structures have undergone remarkable transformation, reflecting broader social, Social media has become an important part of adolescents’ everyday lives, offering opportunities for communication, emotional expression, social support, and access to information, while also presenting potential risks to psychological well-being. This article examines the impact of social media use on adolescent mental health, focusing on social media screen time, cyberbullying, and body-image dissatisfaction. Existing evidence discussed in the article indicates that associations between social media use and mental health are not uniform: some research reports links with depression, anxiety, lower self-esteem, loneliness, sleep-related difficulties, and other forms of psychological distress, whereas other longitudinal evidence suggests that time spent on social media alone may not consistently predict poorer mental health. Cyberbullying emerges as an important risk factor, with reported associations with depression, anxiety, low self-esteem, emotional distress, and suicidal thoughts. The article also highlights concerns surrounding appearance-related social comparison and body dissatisfaction, particularly among adolescent girls. At the same time, social media can support interpersonal relationships and social connectedness when used appropriately. The article concludes by emphasizing the role of parents in establishing healthy media boundaries, encouraging offline interaction and physical activity, monitoring content, modelling balanced media use, and maintaining open communication with adolescents.